High‐mobility self‐aligned top‐gate oxide TFT for high‐resolution AM‐OLED. Issue 11 (11th February 2014) - Morosawa, Narihiro; Nishiyama, Masanori; Ohshima, Yoshihiro; Sato, Ayumu; Terai, Yasuhiro; Tokunaga, Kazuhiko; Iwasaki, Junji; Akamatsu, Keiichi; Kanitani, Yuya; Tanaka, Shinji; Arai, Toshiaki; Nomoto, Kazumasa
Abstract High‐mobility and highly reliable self‐aligned top‐gate oxide thin‐film transistor (TFTs) were developed using the aluminum reaction method. Al diffusion to the oxide semiconductor and homogenization of the oxygen concentration in the depth direction after annealing were confirmed by laser‐assisted atom probe tomography. The high mobility of the top‐gate TFT with amorphous indium tin zinc oxide channel was demonstrated to be 32 cm2/V s. A 9.9‐in. diagonal qHD active‐matrix organic light‐emitting diode (AM‐OLED) display was fabricated using a five‐mask backplane process to demonstrate an applicable solution for large‐sized and high‐resolution AM‐OLEDs.